2007
DOI: 10.1161/circresaha.107.148288
|View full text |Cite|
|
Sign up to set email alerts
|

Augmented Protein Kinase C-α–Induced Myofilament Protein Phosphorylation Contributes to Myofilament Dysfunction in Experimental Congestive Heart Failure

Abstract: Abstract-It is becoming clear that upregulated protein kinase C (PKC) signaling plays a role in reduced ventricular myofilament contractility observed in congestive heart failure. However, data are scant regarding which PKC isozymes are involved. There is evidence that PKC-␣ may be of particular importance. Here, we examined PKC-␣ quantity, activity, and signaling to myofilaments in chronically remodeled myocytes obtained from rats in either early heart failure or end-stage congestive heart failure. Immunoblot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
150
6
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(173 citation statements)
references
References 46 publications
16
150
6
1
Order By: Relevance
“…Although it is well recognized that disturbances in calcium regulation constitute an important mechanism in this process [7], it is now clear that heart failure is also associated with a decline in myofilament response to activator Ca 2+ [15,16,27,37,67,72]. Although isoform distribution and proteolytic cleavage of contractile proteins may play a role, (inappropriate) contractile protein phosphorylation has emerged as an important determinant of depressed myofilament function in various etiologies of heart failure [5,6,27,67]. For example, in experimental heart failure in the rat, we found a depression in myofilament function that was causally linked to alterations in Tn; a follow-up study demonstrated that this was due to, most likely, up-regulation of PKC-α activity and the subsequent phosphorylation of cardiac contractile proteins [5,6].…”
Section: Cardiac Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is well recognized that disturbances in calcium regulation constitute an important mechanism in this process [7], it is now clear that heart failure is also associated with a decline in myofilament response to activator Ca 2+ [15,16,27,37,67,72]. Although isoform distribution and proteolytic cleavage of contractile proteins may play a role, (inappropriate) contractile protein phosphorylation has emerged as an important determinant of depressed myofilament function in various etiologies of heart failure [5,6,27,67]. For example, in experimental heart failure in the rat, we found a depression in myofilament function that was causally linked to alterations in Tn; a follow-up study demonstrated that this was due to, most likely, up-regulation of PKC-α activity and the subsequent phosphorylation of cardiac contractile proteins [5,6].…”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…Although isoform distribution and proteolytic cleavage of contractile proteins may play a role, (inappropriate) contractile protein phosphorylation has emerged as an important determinant of depressed myofilament function in various etiologies of heart failure [5,6,27,67]. For example, in experimental heart failure in the rat, we found a depression in myofilament function that was causally linked to alterations in Tn; a follow-up study demonstrated that this was due to, most likely, up-regulation of PKC-α activity and the subsequent phosphorylation of cardiac contractile proteins [5,6]. Likewise, studies by van der Velden et al indicate that depressed myofilament function in human heart failure is associated with alterations in Tn phosphorylation, as well as other contractile proteins such as myosin light chain and myosin-binding protein C [27].…”
Section: Cardiac Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is involved in numerous cellular processes, such as transcription of DNA, cell death, cell growth, Ca 2+ -handling, and also fine-tunes myofilament function. PKC isoforms have been implicated in several diseases, such as prostate and breast cancer, pulmonary disease, and heart failure (Belin et al 2007;Konopatskaya and Poole 2010;Parker 2003;Parker and Murray-Rust 2004;Sumandea et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory role of PKC may be even larger during cardiac disease, as increased PKC activity and expression levels have been shown in the failing heart (Belin et al 2007;Braz et al 2004;Lamberts et al 2007). …”
Section: Introductionmentioning
confidence: 99%